Pelatihan Penyusunan Skema Gaji Karyawan pada Usaha Menengah di Jakarta - Fortunisa, Ananda; Sadam Suyuthy, Muhammad; Hidayati, Fitri; Putri Herdiana, Friska; Prasamuarso Kuntarto, Guson (LPkM Universitas Bakrie, 2024)
Hard skills-based roll payment training is training in skills to analyze, consider and calculate the factors that must be compensated for employees in their salaries. This training is aimed at medium-sized businesses in Jakarta. The training participants are specifically for medium-sized businesses because medium-sized businesses already have employees and their salaries are fixed. The training consists of 3 sessions, Session 1 is a presentation of material regarding the concept of calculating salaries with the factors that will be included in the salary. In the second session, all participants were given the opportunity to calculate employee salaries at their respective places of business. Furthermore, in the final session, participants were accompanied to calculate their employee payroll in the payroll web application. From the results of this activity, it is known that there are still many medium-sized businesses in Jakarta whose employee salary schemes are only based on the range of employee salaries in the market in general. After participating in this activity, participants will better understand the factors that need to be assessed to be compensated in their employee salary schemes. To develop the innovation of this activity, the payroll web apps prototype was renamed to schemagaji.com. This name change was carried out because the results of observations showed that the name was easier for potential users to remember (potential persona/user). Based on the results of this activity, it is recommended that training related to human resource management for medium-sized businesses be provided more frequently and developed with material at the next level. This is important to do, considering that the training most often provided to medium-sized businesses is material related to product promotion, production systems, digital marketing and business legalization.